Design and validation of a multidimensional vocal scale for teachers´ vocal risk detection - García Real, Teresa; Mendiri, Paula; Díaz Román, Tomás Miguel (Revista de Investigación en Logopedia, 2022)
In the teaching community it is common to misuse the voice so, an early diagnosis is necessary to preserve vocal health. The objective of the study was to design, according to criteria of specificity and simplicity, a vocal multidimensional and reliable scale (EVM-D), that contributes to detect situations of vocal risk of the teacher in the school context. The study involved 299 teachers from 18 randomly selected schools from A Coruña that were divided into two sub-samples, one of them (n =143) for exploratory factor analysis, both with Parallel Analysis and principal axis factorization and oblimin rotation and another sub-sample (n = 156) for confirmatory factor analysis, using the weighted least squares method. After the models were analyzed, the model of three first-order factors (Vocal symptoms, Speech habits and Vocal abuse) and a secondorder one (Vocal risk) was chosen. Goodness-of-fit indices were GFI = ,98, AGFI = ,97, SRMR = ,05; composite reliability (FC) was ,80; ,70 and ,73 and the mean variance extracted (AVE) in the three factors was ,44; ,43 and ,47 respectively; the FC of the first order factor was ,83 and the AVE, ,63. Cutt-off values were obtained according to sex for de vocal risk percentiles P90, P75 y P60: High, medium, low and very low. EVM-D as a reliable and consistent scale could be useful to detect etiological factors or symptoms and apply early and autonomously vocal hygiene by the teacher.